Male wing variation in the Cuban cockroach Byrsotria fumigata (Guérin-Méneville, 1857) (Blattodea: Blaberidae) - Reinier Núñez-Bazán (Revista Chilena de Entomología, 2021)
Byrsotria fumigata (Guérin-Méneville, 1857) is an endemic cockroach from Cuba which presents a remarkable variability in the male wings. This contribution addresses the differences in size and wing shape of males, previously reported on the literature. Brachypterous individuals are illustrated and the wing variation is quantified. The distribution of the species is expanded with two new localities.